PEMBERIAN LAYANAN DAN EDUKASI AFO (ANKLE FOOT ORTHOSIS) BAGI ANAK CEREBRAL PALSY DENGAN EKONOMI KURANG MAMPU - Syafi'ie, Hisyam (Tahta Media Grup, 2024)
Children diagnosed with cerebral palsy will have problems walking. Control of one's muscles is impaired by cerebral palsy (CP). A child with cerebral palsy may contract their muscles excessively, very little, or all simultaneously. It's probable that limbs stiffen up and take odd positions. The limbs may tremble, wobble, or hang due to fluctuating contractions of the muscles. Cerebral palsy can also impact posture, balance, and physical coordination. Things like sitting, standing up, and walking will be challenging. Ankle foot orthoses, or AFOs, are a type of therapy that can assist children with cerebral palsy improve their locomotor motor function. Research on the impact of AFO use on these children's walking balance is one way to address this issue.